Solvent-free and rapid synthesis of mesoporous Pt–iron oxide catalysts via mechanochemical assembly. Issue 15 (9th July 2019) - Zhou, Min; Zhao, Jiahua; Zhang, Pengfei; Chen, Nanqing; Yang, Shize
Abstract : Mechanochemical assembly enables the solvent-free construction of plentiful mesopores and highly dispersed Pt NPs in iron oxide catalysts. Abstract : Mesoporous Fe x O y and Pt@Fe x O y have demonstrated promising performance in catalysis. However, current methods usually use wet chemistry, which poses several drawbacks. In this study, we introduce a simple process of mechanochemical assembly between an iron salt and a triblock copolymer in the solid state that can not only directly form abundant mesopores into Fe x O y, but also enable a high dispersion of Pt species at the nm or sub-nm scale. In this regard, mesoporous Fe x O y and Pt@Fe x O y catalysts with high surface areas (up to 149 m 2 g −1 ) and narrow pore size distributions (∼5 nm) can be obtained in a solvent-free and rapid (0.5 h) way. The kinetic energy and frictional heating of ball milling are expected to promote the interaction and diffusion between iron precursors and surfactants, while the solvent-free feature confines their assembly to the mesophase of the P123 copolymer. Moreover, these Pt@Fe x O y catalysts provide good activity in the total oxidation of propylene and CO.